The Man Who Built Boxes: And Other Stories - Tavares, Frank (Bacon Press Books, 2013)
Keywords: Short stories; American; dept.com

Direct-to-consumer (DTC) antidepressant advertising and consumer misperceptions about the chemical imbalance theory of depression: the moderating role of skepticism - Park, Jin Seong; Ahn, Ho-Young (Health Marketing Quarterly, 2013)
Based on a survey with members of an online consumer panel (N= 699), this study revealed that: (a) a substantial percentage of consumers held misperceptions about the chemical imbalance theory of depression; (b) personal and interpersonal experiences with depression positively related to such misperceptions; (c) overall, exposure to direct-to-consumer (DTC) antidepressant advertising did not significantly relate to misperceptions; and (d) DTC exposure magnified misperceptions when consumers were highly trustful of DTC advertising, whereas exposure diluted misperceptions when consumers were highly skeptical. Theoretical and practical implications of the research are discussed, especially in light of the social responsibility of DTC advertising. © 2013 Copyright Taylor and Francis Group, LLC.
5 citations (Crossref) [2023-10-31] Citation Key Alias: pop00284 tex.type: [object Object]
Keywords: Advertising as Topic; Antidepressive Agents; Brain Chemistry; Depression; Female; Health Knowledge; Attitudes; Practice; Humans; Male; advertizing; antidepressant agent; attitude to health; brain level; depression; dept.com; direct-to-consumer (DTC) prescription drug advertising; drug effects; female; health beliefs; human; male; procedures; skepticism toward advertising; social responsibility of advertising

Interaction effects of perceived sponsor motives and facebook credibility on willingness to visit social cause facebook page - Lee, Yoon-Joo; Ahn, Ho-Young (Journal of Interactive Advertising, 2013)
19 citations (Crossref) [2023-10-31] Citation Key Alias: pop00202 tex.type: [object Object]
Keywords: dept.com

Communication strategies in cosmetic surgery websites: an application of Taylor's six-segment message strategy wheel. - Ahn, Ho-Young Anthony; Wu, Lei; Taylor, Ronald E (Health marketing quarterly, 2013)
Using Taylor's six-segment message strategy wheel as a theoretical framework, this study examines the communication approach (transmission or ritual) and message strategy (ego, social, sensory, routine, acute need, or ration) of cosmetic surgery websites. A content analysis revealed a fairly even division between transmission and ritual approaches. Ration strategy was the exclusive strategy in the websites adopting a transmission approach. No routine or acute need strategies were observed. Websites incorporating the ritual approach used ego, social, and sensory strategies. Human female models and natural objects were incorporated to deliver emotional persuasion. Implications for cosmetic surgery web marketers are discussed.
12 citations (Crossref) [2023-10-31] Place: England Ahn, Ho-Young Anthony. Department of Communication, Southern Connecticut State University, New Haven, Connecticut 06515, USA. ahnh1@southernct.edu
Keywords: *Communication; *Marketing of Health Services/mt [Methods]; *Surgery; Plastic; Communication; Emotions; Female; Humans; Internet; Marketing of Health Services; Models; Theoretical; Motivation; Surgery; Plastic; Surgery; Plastic/px [Psychology]; Taylor's six-segment message strategy wheel; United States; article; content analysis; cosmetic surgery; dept.com; emotion; female; financial management; human; interpersonal communication; methodology; motivation; physician advertising; plastic surgery; psychological aspect; theoretical model